Thermoplastic Starch (TPS)/Polylactic Acid (PLA) Blending Methodologies: A Review (2021)
Polylactic acid (PLA) and thermoplastic starch (TPS) are biodegradable polymers of biological origin, and the mixture of these polymers has been studied due to the desirable mechanical properties of PLA and the low processing cost of TPS. However, the TPS/PLA combination is thermodynamically immiscible due to the poor interfacial interaction between the hydrophilic starch granules and the hydrophobic PLA. To overcome these limitations, researchers studied the modification, processing, and properties of the mixtures as a strategy to increase the compatibility between phases. This review highlights recent developments, current results, and trends in the field of TPS/PLA-based compounds during the last two decades, with the main focus of improving the adhesion between the two components. The TPS/PLA blends were classified as plasticized, compatible, reinforced and with nanocomposites. This article presents, based on published research, TPS/PLA combinations, considering different methods with significant improvements in mechanical properties, with promising developments for applications in food packaging and biomedicine